Optimization of root canal system disinfection using laser - K. N. Kerimova; I. V. Bagdasarova; M. K. Makeeva; A. V. Zoryan; V. E. Magay; N. L. Lezhava; A. I. Markova (LLC "Endo Press", 2020)
Relevance. When using drug irrigants during endodontic treatment it is not always possible to achieve complete disinfection in the root canals, as well as in periapical tissues. This literature review aims to identify the effectiveness of the disinfecting effect of lasers in the root canals compared to other protocols. Aim. To identify the effectiveness of using lasers as a disinfectant in the root canals. Materials and methods. The literature was selected through the following databases PubMed, Google Scholar, eLibrary and Embase (Elsevier). Keywords that were used: lasers, endodontics, disinfection, photodynamic therapy. The search was limited to English and Russian language publications published from 2001 to 2018.Results. A total of 49 articles were identified. After their selection by the criteria of inclusion and removal of duplicate articles, the total number became 12.Conclusions. Lasers are effective as disinfectants in root canals, especially erbium lasers. The best activity is observed when they are used together with NaOCl. It should also be remembered that if we used lasers incorrectly, they can harm healthy tissues.